POG06 Development and validation of a quality of life scale for mitochondrial disease (Mito-QoL). Issue 11 (22nd October 2010) - Gorman, G; Turnbull, D M; Horvath, R; Whittaker, R; Phillips, A; Cadogan, M; Elson, J L; McColl, E; Apabhai, S; MaFarland, R
Abstract : Introduction: Mitochondrial diseases are a clinically multifarous group of genetic disorders with extensive phenotypic and disease burden variability. Health related quality of life (HRQoL) is increasingly recognised as a fundamental patient-based outcome measure in both clinical intervention and research. Generic HRQoL outcome measures have been extensively validated across populations and different disease states. Due to their inclusive construct not all relevant aspects of a specific illness may be captured. It is acknowledged that there is a need to develop disease-specific HRQoL measures that centre on symptoms characteristic of a specific disease or condition. This study presents the conceptualisation, development and assessment of a disease-specific HRQoL measure (Mito-QoL) for patients with mitochondrial cytopathies. Methods: Domain and item content for the Mito-QoL was derived from semi-structured key-informant interviews and modified following piloting of the questionnaire by post. Items were eliminated with the use of standard psychometric criteria. Construct validity was assessed by comparing domain scores with similar Short Form 36 domains. Results: Mito-QoL consists of 63 items within 16 unidimensional domains demonstrating excellent internal reliability (Cronbach's α>0.74) and construct validity. Conclusion: Mito-QoL is a valid and reliable disease-specific HRQoL measure which may be of use in clinical practice and research.